KEBIJAKAN PEMERINTAH DALAM UPAYA MENINGKATKAN KEMAMPUAN DAYA BELI MASYARAKAT MELALUI PASAR MURAH - Muhammad Masshaumi; Hery Sukriadi; Suyanti; Abang Indriyadi; Dr. Yulius Yohanes, M.Si (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The low-price market (pasar murah) is one of the government's policy instrumentsaimed at stabilizing prices and enhancing the purchasing power of the population,particularly low-income groups. This study analyzes the effectiveness of the pasarmurah policy within the context of Indonesia's domestic economy in the post-COVID-19 pandemic period and amidst global inflationary pressures. Using adescriptive qualitative approach, the research explores the implementationmechanisms of the pasar murah program, stakeholder involvement, and its impacton purchasing power and the price stability of essential goods. The findingsindicate that the pasar murah initiative contributes positively to maintaining thebalance between supply and demand, while also providing affordable access toessential commodities for impoverished communities. However, the policy'simplementation still faces challenges such as inter-institutional coordinationissues, budget constraints, and the need for ongoing evaluation to improve futureexecution. This study recommends strengthening central-local governmentsynergy, enhancing transparency in distribution, and expanding the geographicaland commodity coverage of pasar murah as part of a long-term strategy toimprove societal welfare.